Revolutionizing Horticultural Crop Improvement: A Comprehensive Review of MAGIC Breeding - Akhilraj, B. C.; Suresh, J.; Nireshkumar, N.; Raghul, S.; Kumar, M. (International Journal of Economic Plants, 2024)
MAGIC (Multiparent Advanced Generation Inter-Cross) breeding is a powerful approach that has gained significant attention in horticultural crop improvement. By inter crossing multiple diverse parental lines over multiple generations, MAGIC breeding aims to capture and combine genetic diversity to enhance desirable traits in the offspring. Magic breeding focuses on enhancing traits such as yield, quality, disease resistance, and stress tolerance in horticultural crops such as fruits, vegetables, ornamentals, and herbs. This method harnesses the power of genetic diversity within plant populations, utilizing advanced tools such as marker-assisted selection, genomic selection, and gene editing to accelerate the breeding process and achieve targeted outcomes. Overall, MAGIC breeding represents a promising avenue for sustainable horticultural crop improvement, offering opportunities to create cultivars that are more productive, resilient, and nutritious, thereby contributing to food security, environmental sustainability, and economic prosperity in agriculture. This review provides a comprehensive analysis of the principles, applications, and advantages of MAGIC breeding in horticultural crops. It explores the breeding process, the impact on genetic variation, trait improvement, and the potential for discovering novel gene combinations. Additionally, the review discusses the challenges, current progress, and future prospects of MAGIC breeding, shedding light on its potential to revolutionize horticultural crop improvement.